A comprehensive study on the electronic, optical, and light harvesting examination of mixed cation 2-Br-PEAI/FAPbI3 perovskite solar cells through first principles calculations and numerical simulations - Mohammed Benali Kanoun; Adil Alshoaibi; Mousaab Belarbi; Souraya Goumri-Said (Results in Chemistry)
In this study, we explore the electronic structures, optical characteristics, and solar cell performance of the mixed 2-Br-PEAI/FAPbI3 perovskite surface using first-principles calculations and modeling simulation. The results reveal that the mixed 2-Br-PEAI/FAPbI3 surface exhibits a band gap of 1.92 eV and a notably high absorption coefficient on the scale of 105 cm−1. Analysis of optical spectra highlights strong absorption coefficients across both visible and ultraviolet regions, indicating efficient energy harvesting from visible light. These findings carry significant implications for the advancement of solar cell device. Using the SCAPS-1D device simulator, we conducted numerical analyses to assess the performance of devices based on mixed 2-Br-PEAI/FAPbI3. Our simulations unveiled that the device architecture featuring FTO/SnO2/mixed 2-Br-PEAI/FAPbI3/Spiro-OMeTAD/MoOx/ITO/Cu achieved notable photoconversion efficiency, reaching up to 23.1 %. Remarkably, this performance closely parallels experimental measurements, indicating that the incorporation of MoOx/ITO layers contributes substantially to enhancing the overall efficiency of mixed perovskite-based solar cells.